THE EFFECT OF HERRINGBONE TECHNIQUE TOWARD STUDENTS READING COMPREHENSION OF RECOUNT TEXT AT THE GRADE VIII STUDENTS OF SMPN 4 RAMBAH HILIR - Firda, Nurjani (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2016)
Nurjani Firda, 2016. The Effect of Herringbone Technique toward Students` Reading Comprehension of Recount Text at the Grade VIII Students of SMPN 4 Rambah Hilir. The purposes of this research were to find out students` reading comprehension of recount text taught by using Herringbone technique and taught without using Herringbone technique. And to find out whether there was a significant effect of using Herringbone technique toward students reading comprehension of recount text at the grade VIII students of SMPN 4 Rambah Hilir. This research was an experimental research, precisely a pre-experimental research. The design of this research was one group pretest and posttest design. There were eight meetings in giving treatments. The instrument of this research was test multiple choices. The participants were students at grade VIII of SMPN 4 Rambah Hilir. The research findings showed that the improvement from the score of t-test. The total score of t-test was 4.433. Based on t-table, 2.00 <4.433 > 2.65. Therefore, it could be concluded that there was a significant effect of using Herringbone Technique toward students reading comprehension of recount text at the grade VIII students of SMPN 4 Rambah Hilir.